Decellularized Human Stromal Lenticules Combine with Corneal Epithelial-Like Cells: A New Resource for Corneal Tissue Engineering - Shuai Qin; Shuai Zheng; Bing Qi; Rui Guo; Guanghui Hou (Stem Cells International)
The lack of donor corneal tissue or the immunological rejection remains a challenge for individuals with limbal stem cell deficiency (LSCD) who are treated with keratoplasty. Numerous lenticules which were extracted by small incision lenticule extraction (SMILE) appear to be useful materials for keratoplasty. In order to reduce the incidence of allograft rejection, lenticules would be decellularized. Lenticules which were treated with liquid nitrogen and nucleases had no cellular and nuclear materials remained. Human induced pluripotent stem cells (iPSCs) can be generated from the patient who requires keratoplasty, offering an autologous alternative and eliminating the risk of graft rejection. We found that BMP-4, RA, N-2 supplement, hEGF, B27, decellularized human stromal lenticules, conditioned medium, or induction medium promoted the differentiation of human iPSCs with high purity. The results showed that human iPSCs cultured for 4 days in differentiation medium A, 14 days in condition medium, and 1 week in induction medium on decellularized human stromal lenticules developed markedly higher expression of the markers P63, CK3, and CK12 than did those in the other methods. The level of gene expression of the epithelial and pluripotency markers and analysis by scanning electron microscopy and immunohistochemistry also showed successful differentiation. After inducing differentiation in vitro, corneal epithelial-like cells were induced. In the study, we investigated the possibility of a new resource for corneal tissue engineering.